Deconstructing Williamsburg: Using focus groups to examine residents' perceptions of the building of a walkable community - Sharratt Michael T; Kaczynski Andrew T (BMC, 2010)
Abstract Background Components of the built environment are associated with active living behaviors, but research in this area has employed surveys and other quantitative methods almost exclusively. Qualitative approaches can provide additional detail about how neighborhoods influence physical activity, including informing the extent to which such relationships are causal in nature. The purpose of this study was to gain an in-depth understanding of residents' attitudinal and behavioral responses to living in a neighborhood designed to be walkable. Methods Focus groups were conducted with residents of a planned retail and residential development that was designed to embody many attributes of walkability and was located within a large city in southwestern Ontario. In total, 31 participants provided qualitative data about neighborhood resources and dynamics, use of local services, physical activity behavior, and other related issues. The data were transcribed and coded for themes relevant to the study purpose. Results Salient themes that emerged emphasized the importance of land use diversity, safety, parks and trails, aesthetics, and a sense of community, with the latter theme cutting across all others. The data also revealed mechanisms that explain relationships between the built environment and behavior and how sidewalks in the neighborhood facilitated diverse health behaviors and outcomes. Finally, residents recited several examples of changes in behavior, both positive and negative, since moving to their current neighborhood. Conclusions The results of this study confirmed and expanded upon current knowledge about built and social environment influences on physical activity and health. That many residents reported changes in their behaviors since moving to the neighborhood permitted tentative inferences about the causal impact of built and social environments. Future research should exploit diverse methods to more fully understand how neighborhood contexts influence active living.